Discovered, made visible, constructed, and left out: LGBT+ parenting in the Italian sociological debate. Issue 2 (4th March 2023) - Monaco, Salvatore; Nothdurfter, Urban
ABSTRACT: When, how, and which disciplines started to deal with which forms and aspects of LGBT+ parenthood is not a coincidence but is linked to occasions of discussion as well as to visibility, acceptance, and recognition in the wider social and political contexts. This particularly applies to sociological contributions which look at families and parenting involving relations to social institutions and their impact and shaping of forms, challenges, and meanings of parenting and family life. In Italy, issues about LGBT+ parenting began to appear in the sociological literature some thirty years ago. Since then, the debate has seen different waves and shifts, which show both how external movements, occasions, and discussions influenced the sociological debate and how the latter has, in turn, contributed to the construction and recognition of the phenomenon. Against this background, using a data mining approach, the article presents an analysis of the most recent sociological literature on LGBT+ parenting, highlighting the main dimensions of the debate and outlining expressions, concepts, and words most used on this topic. Using Italian sociology as an example, the critical analysis of these findings shows how issues of topicality and (in)visibility are both reflected and reiterated by contextual sociological discourses and debates.